Rh(III)‐Catalyzed Synthesis of Multisubstituted Isoquinolines from Benzylamines and Diazo Compounds. Issue 8 (14th March 2017) - Lin, Xing; Chauvin, Remi; Yu, Yunliang; Wang, Lianhui; Xu, Linhua; Cui, Xiuling
Abstract: Multisubstituted isoquinolines have been prepared by Rh(III)‐catalyzed cyclization of benzylamines with diazo compounds via aryl C−H bond activation using molecular oxygen from air as an oxidant. This method features mild reaction conditions, simple catalytic system, tolerance of a broad range of substrates, high efficiency and regioselectivity. Abstract : Multisubstituted isoquinolines have been prepared by Rh(III)‐catalyzed cyclization of benzylamines with diazo compounds via aryl C−H bond activation using molecular oxygen from air as the oxidant. This method features mild conditions, a simple catalytic system, toleration of a broad range of substrates, and high efficiency and regioselectivity.